Sodium Thiosulfate Reduces Acute Kidney Injury in Patients Undergoing Cytoreductive Surgery Plus Hyperthermic Intraperitoneal Chemotherapy with Cisplatin: A Single-Center Observational Study - Kurreck, Annika; Gronau, Felix; Vilchez, Miguel Enrique Alberto; Abels, Wiltrud; Enghard, Philipp; Brandl, Andreas; Francis, Roland C. E.; Foehre, Bettina; Lojewski, Christian; Pratschke, Johann; Thuss-Patience, Peter; Modest, Dominik; et al. (Annals of Surgical Oncology, 2022)
Background: Cytoreductive surgery (CRS) in combination with hyperthermic intraperitoneal chemotherapy (HIPEC) represents a multimodal treatment concept for patients with peritoneal surface malignancies. The use of intraperitoneal cisplatin (CDDP) is associated with a risk of acute kidney injury (AKI). The aim of this study is to evaluate the protective effect of perioperative sodium thiosulfate (STS) administration on kidney function in patients undergoing CRS and CDDP-based HIPEC. Patients and Methods: We retrospectively analyzed clinical data of all patients who underwent CRS and CDDP-based HIPEC at our hospital between March 2017 and August 2020. Patients were stratified according to the use of sodium thiosulfate (STS vs. no STS). We compared kidney function and clinical outcome parameters between both groups and determined risk factors for postoperative AKI on univariate and multivariate analysis. AKI was classified according to acute kidney injury network (AKIN) criteria. Results: Of 238 patients who underwent CRS and CDDP-based HIPEC, 46 patients received STS and 192 patients did not. There were no significant differences in baseline characteristics. In patients who received STS, a lower incidence (6.5% vs. 30.7%; p = 0.001) and severity of AKI (p = 0.009) were observed. On multivariate analysis, the use of STS (OR 0.089, p = 0.001) remained an independent kidney-protective factor, while arterial hypertension (OR 5.283, p < 0.001) and elevated preoperative urea serum level (OR 5.278, p = 0.032) were predictors for postoperative AKI. Conclusions: The present data suggest that STS protects patients from AKI caused by CRS and CDDP-based HIPEC. Further prospective studies are needed to validate the benefit of STS among kidney-protective strategies.
CRIS-Team Scopus Importer:2022-11-17